Cytological, physiological, and transcriptomic analyses of golden leaf coloration in Ginkgo biloba L - Li, Wei-xing (Hortic Res, 2018)
Ginkgo biloba is grown worldwide as an ornamental plant for its golden leaf color. However, the regulatory mechanism of leaf coloration in G. biloba remains unclear. Here, we compared G. biloba gold-colored mutant leaves and normal green leaves in cytological, physiological and transcriptomic terms. We found that chloroplasts of the mutant were fewer and smaller, and exhibited ruptured thylakoid membranes, indistinct stromal lamellae and irregularly arranged vesicles. Physiological experiments also showed that the mutant had a lower chlorophyll, lower flavonoid and higher carotenoid contents (especially lutein). We further used transcriptomic sequencing to identify 116 differentially expressed genes (DEGs) and 46 transcription factors (TFs) involved in chloroplast development, chlorophyll metabolism, pigment biosynthesis and photosynthesis. Among these, the chlorophyll biosynthesis-related PPO showed down-regulation, while chlorophyll degradation-related NYC/NOL had up-regulated expression in mutant leaves. Z-ISO, ZDS, and LCYE, which are involved in carotenoid biosynthesis were up-regulated. Quantitative real-time PCR (RT-qPCR) further confirmed the altered expression levels of these genes at three stages. The alteration of PPO and NYC/NOL gene expression might affect chlorophyll biosynthesis and promote degradation of chlorophyll b to chlorophyll a, while the up-regulated genes Z-ISO, ZDS and LCYE enhanced carotenoid accumulation. Consequently, changes in the ratio of carotenoids to chlorophylls were the main factors driving the golden leaf coloration in the mutant G. biloba.